Effect of short-term guided aerobic exercise and diet intervention on overweight women - Kauko, Kirsi (2010)
Abstract Effect of Short-Term Guided Aerobic Exercise and Diet Intervention on Overweight Women Kauko, Kirsi LLTS007 Master’s Thesis of Sport Medicine University of Jyväskylä, Faculty of Sport and Health Sciences, Department of Health Sciences Spring 2010, 68 pages, 6 appendices Overweight or obese persons have substantially increased risk for multiple chronic disorders, for example type 2 diabetes (T2D), dyslipidemia, hypertension and cardiovascular disease (CVD). Physical activity or exercise has an important role in the prevention and treatment of obesity related illnesses, for example T2D, CVD and metabolic syndrome (MetS). The main goal of this Master’s thesis is to study the possible effects of short-term aerobic exercise and diet intervention on body composition, blood lipid profile and glucose metabolism, as well as on the risk factors of metabolic syndrome on overweight/obese women and to compare the groups with an added motivational factor or general exercise/diet guidance. The subjects were enrolled in the Exercise and Weight Control Intervention (EWI-09) study carried out at the University of Jyväskylä in the Department of Health Sciences in summer-winter 2009. Ninety-four previously physically inactive (participating regular leisure time aerobic exercise less than two times per week, less than 45 min per session), overweight and obese women aged 20-50 years were randomly assigned into exercise (EX: body mass index > 25-33 kg/m2) or weight control (WC: BMI > 25-38 kg/m2) groups. They were further assigned into exercise with wrist computer (EXW), exercise control (EXC), weight control with wrist computer (WCW) and weight control control (WCC). Eighty subjects completed the study (EXW n=21, EXC n=19, WCW n=20, WCC n=20). Exercise group underwent a progressive, supervised exercise program (Nordic Walking) according to ACSM’s guidelines of exercise for health promotion. The WC group received dietary instructions from a clinical nutritionist according to the guidelines of Finnish nutrition recommendations targeting weight loss. Fasting blood samples were drawn, anthropometric measurements (height, weight, BMI, waist circumference, body composition), 10m walking test and VO2 max –tests were performed. SPSS 15.0 for Windows was used to carry out statistical analyses. We found that the exercise group had significant reduction of their Free Fatty Acids (FFA EXW p=0.001, EXC p=0.001) and glucose metabolism (f-Gluc EXW p<0.001, EXC p=0.01) without therapeutic weight loss after 6-week intervention. The weight control group reduced their body weight, BMI and Visceral Fat Area. In addition, subjects in the exercise group with the wrist computer significantly reduced waist circumference (p=0.01), Insulin (p=0.01) and risk factors of the metabolic syndrome (p=0.04). In conclusion, aerobic exercise, with progressive moderate intensity has health benefits without therapeutic weight loss in short time. Exercise is more effective than diet for reducing the risk factors of metabolic syndrome.